Impact of tillage type and soil texture to soil organic carbon storage: The case of Ethiopian smallholder farms - Alemayehu, N.; Masafu, M.M.; Ebro, A.; Tegegne, Azage (Academic Journals, 2016)
Soil organic carbon is a fundamental soil resource base. However, there is limited information on soil organic carbon storage due to influence of tillage type and soil texture under smallholder production systems in Ethiopia. The objective of this study was therefore to quantify soil organic carbon in different soil textures and tillage types; and to the contribution of livestock in improving soil carbon, soil structure and soil fertility. Fifteen sample sites were selected for soil chemical analysis details on crops, soil and land management practices for each sample site was collected through household interviews, key informants discussion and literature review. The carbon storage per hectare for the four soil textures at 0 to 15 cm depth were 68.4, 63.7, 38.1 and 31.3 t/ha for sandy loam, silt loam, loam and clay loam; respectively. Sand and silt loams had nearly twice the organic carbon content than loam and clay loam soil. The soil organic carbon content for tillage type at 0 to 15 cm was 8.6, 10.6, 11.8 and 19.8 g kg-1for deep tillage, minimum tillage, shallow tillage, and zero tillage; respectively. Among tillage types soil organic carbon storage could be increased by using the minimum and shallow tillage. Carbon saved due to shallow cultivation as practiced by Ethiopian smallholders using oxen drawn plough contributed to carbon trade off of about 140 million ton per year. At current levels of carbon saving shallow tillage would generate $4.2 billion of revenue per year for Ethiopian smallholders.